Education and competence mismatches: job satisfaction consequences for workers - López Nicolás, Ángel; Badillo Amador, Lourdes; Vila Lladosa, Luís E. (Rect@, 2008)
The accuracy of the match in the job-worker pairing is analyzed both in terms of education and in terms of qualification using Spanish data from the 2001 wave of the European Community Household Panel (ECHP). Regarding the incidence of mismatch situations, the results suggest that the education match appears to be a rather poor indicator for the qualification match. In addition, ordered discrete choice models reveal that they have different consequences in terms of job satisfaction as well.